An interregional, transdisciplinary and good practice-based approach for frailty: The Mind&Gait project - Apóstolo, J.; Couto, F.; Bobrowicz-Campos, E.; Dixe, M. A.; Ribeiro, J.; Braúna, M.; Camacho, T.; Santos-Rocha, R.; Parreira, P.; Cruz, A.; Malça, C.; Dantas, C.; et al. (Translational Medicine @ UniSa, 2019)
Social facilities such residential structures and day-centres increasingly seek integrated, structured, adapted, creative, dynamic and economic strategies to prevent frailty. The arising need of an aged and frail population requires innovative interventions and products to prevent cognitive and physical decline. The interregional MIND&GAIT project aims to promote independent living in frail older adults by improving cognition and gait ability by using assistive products. This transdisciplinary strategy within a 24-months period expects as project' deliverables: i) a structured and good practice-based combined intervention (CI) consisting of a cognitive stimulation programme and a physical exercise programme; ii) an auto-blocking mechanism for rolling walkers with biofeedback acquisition (ABMRW); iii) a randomized clinical trial to assess CI' effectiveness; and iv) a web-platform to be used as a repository that will support and disseminate the intervention materials, covering the action-line of translational research. Positive benefits are expected in prevention and maintenance of frail older adults' capacities. Preliminary results showed positive effects on the improvement of cognitive and physical functions, functionality and depressive symptomatology. The interregional geographical coverage induced by MIND&GAIT underlines the potential replicability of the project extension to the community in the Centro and Alentejo regions of Portugal. MIND&GAIT network supports actions and provides learning opportunities and emergence of locally-embedded support systems towards social innovation for older adults.